International Access to Administrative Data for Germany and Europe - Stefan Bender; Anja Burghardt; David Schiller (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2014)
In the last years access to research data has made a lot of progress in EU countries. Nevertheless transnational access to confidential microdata - although there are some developments like Data without Boundaries - is still complicated and needs improvement. The first part of the paper describes the (international) access to highly sensitive German administrative labour market data and how this international access is expanded within the research data centre in research data centre (RDC in RDC) approach. In the second part a broader view of international access to official microdata in the EU will be given. Starting with a brief overview of the EU-funded project Data without Boundaries (DwB) a possible roadmap for international access in Europe and beyond is presented.
Keywords: 330